CULTURE, SCIENCE AND PHILOSOPHY OF KNOWLEDGE - M.N.Abdullaeva; G.T.Makhmudova (Scholar Express Journal, 2024)
The purpose of this scientific research is to identify the complex phenomenon of science as an axiological and humanistic phenomenon, which is a producer of the culture and consciousness of humanity. The relevance of the study is because the authors reveal science as a complex cultural phenomenon. Its historically determined task is the evolution of value orientations and transformations in the context of the commercialization of modern science. In this regard, this article is aimed at identifying or disclosing pressing problems in an unstable globalizing world, where many issues are resolved by the dominant technogenic consciousness of modern society, dictating its laws and guidelines through the prism of exceptional profits, benefits and consumer sustainability. The leading approach (or method) to the study of this problem is a systematic approach, which allows us to comprehensively consider structural-functional, methodological, and chronological problems in the context of feedback theory, helping to identify an objective picture of the task at hand. The article presents an analysis of the philosophy of science in the second half of the twentieth century. and the beginning of the 21st century. marked a fundamental change in the study of reality. In the process of cognition, new philosophical ideas, new methodological approaches, scientific concepts, etc. emerged, different from the previous ones. In epistemological terms, for adequate cognition from the standpoint of modern epistemology, new concepts are formed (complexity, self-organization, chaos, etc.), and at the same time, some concepts (randomness, uncertainty, chaos, etc.)
Keywords: philosophy; methodology; axiology